Modeling the impact of drug interactions on therapeutic selectivity - Zohar B. Weinstein (Nature Portfolio, 2018)
While drugs can interact in both target and off-target cell types, more favorable interaction in the target cell may nevertheless allow for a therapeutic window. Here, the authors show, using two yeast species as a model, that differential drug interactions indeed adjust the selective window.